2003
DOI: 10.1097/00001756-200304150-00011
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and temporal stimulus characteristics in the processing of abstract auditory features

Abstract: The processing of abstract stimulus features in the human brain was studied by presenting the subjects with frequent standard tone pairs and infrequent deviant tone pairs. Both pairs varied randomly over a wide frequency and/or intensity range, there being no physically constant standard stimulus. The common feature of the standard pairs was the direction of change within the pair, e.g. the second tone was louder in intensity and/or higher in frequency than the first tone. Deviant pairs, having opposite featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…Several studies showed that varying the absolute frequency levels of tone pairs while keeping either only the direction or both the direction and the relative size of the within-pair pitch step constant allows the formation of a representation against which tone pairs with a different pitch step elicit the MMN (Paavilainen et al, , 2003Saarinen et al, 1992). Similar results were obtained in newborn infants (Carral et al, 2005;Stefanics et al, 2009) as well as for tonal patterns and short melodies (Fujioka et al, 2004;Tervaniemi et al, 2001Tervaniemi et al, , 2006Trainor et al, 2002).…”
Section: Low-level Variability -Higher-level Regularitymentioning
confidence: 58%
See 1 more Smart Citation
“…Several studies showed that varying the absolute frequency levels of tone pairs while keeping either only the direction or both the direction and the relative size of the within-pair pitch step constant allows the formation of a representation against which tone pairs with a different pitch step elicit the MMN (Paavilainen et al, , 2003Saarinen et al, 1992). Similar results were obtained in newborn infants (Carral et al, 2005;Stefanics et al, 2009) as well as for tonal patterns and short melodies (Fujioka et al, 2004;Tervaniemi et al, 2001Tervaniemi et al, , 2006Trainor et al, 2002).…”
Section: Low-level Variability -Higher-level Regularitymentioning
confidence: 58%
“…Dots within a pair had identical color in most cases and the probabilities of the different colors were equiprobable within the sequence, overall. Infrequent dot-pattern pairs, the second stimulus of which had a different color than the first one, elicited the vMMN response (for similar results in the auditory modality, see Paavilainen et al, 1999Paavilainen et al, , 2003Saarinen et al, 1992). Finding MMN and vMMN to violations of these rules hint at predictive processing, because the rules allowed predicting some feature of a stimulus from the immediately preceding one.…”
Section: Predictive Memory Representationsmentioning
confidence: 86%
“…Similarly, in an EEG study where both local and global stimulus features were manipulated, MMN was mainly observed for global deviation (List et al, 2007). The extraction of abstract features goes beyond frequency-based rules as demonstrated by a further EEG study (Paavilainen et al, 2003). In this study, tone-pairs with ascending or descending frequency relations or with increasing and decreasing intensity relations were presented in series that were interrupted by an opposite frequency transition.…”
Section: Introductionmentioning
confidence: 70%
“…Our finding that a repeated sound interrupting a series of sweeps that alternately change their FM direction elicits an enhanced MEG response could be taken as evidence for a higher-order representation of the alternating tone series. Evidence for such abstract rule representation has been described in previous EEG and MEG studies (Tervaniemi et al, 1994;Paavilainen et al, 2003). In addition, a previous EEG study has described the phenomenon of repetition negativity: a repetition within a constantly changing sound stream leads to an MMN-like response within 100e200 ms after stimulus onset (Horvath et al, 2001).…”
Section: Mmnm For Abstract Rule Violations?mentioning
confidence: 79%
“…Partial additivity has been found in the auditory system, in detection of deviants in simple acoustical features such as frequency, stimulus onset asynchrony, and intensity (Paavilainen, Valppu & Näätänen, 2001). However, no such additivity effect has been found to deviants in higher order abstract features, such as intensity or pitch change in pairs of tones varying in the absolute pitch or intensity values (Paavilainen et al, 2003), suggesting that the additivity hypothesis may not be valid within more complex musical contexts.…”
Section: Motivic Pacementioning
confidence: 99%